Structural Competency: Evaluation of Qualitative Results of Pilot Study - Calogero, Christie (East Carolina University, 2022)
Structural competency is an approach to training healthcare providers to address social and structural barriers that impede certain communities from receiving equal and quality healthcare. The purpose of this project was to 1) explore the published literature regarding structural competency and how it has been applied in healthcare professional training, and 2) analyze the qualitative data from an educational pilot study implementing an adapted structural competency curriculum for acceptability, appropriateness, and feasibility. Literature searches were conducted in PubMed and CINHAL Plus with Full Text, as well as a manual search of the https://structuralcompetency.org/ website. A total of 111 articles were retrieved after duplicates were removed, ten (N=10) studies met the inclusion criteria, and findings are synthesized to describe the timing and settings of the structural competency training, types of teaching and learning activities used, measurements of outcomes and the levels of proficiency achieved. After this review, content analysis was used to examine the qualitative data from the structural competency pilot education study called Health Equity Advanced Through Structural Competency (HEAT-SC). Results from this preliminary data support that an adapted structural competency curriculum was acceptable, appropriate, and feasible. These results suggest that the adapted curriculum could be implemented on a larger scale to contribute to the fight against health inequities in eastern North Carolina.
Keywords: Structural competency; Pilot study